History of cardiac and thoracic surgeryA cardiac surgeon, his way to holiness, and his heritage – the 80th anniversary of Giancarlo Rastelli’s birthday and the 45th anniversary of the first Rastelli procedure - Mazurak, Magdalena; Kusa, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Cardiac surgeon Giancarlo Rastelli was born 80 years ago in Pescara, Italy. His name was immortalized in such eponyms as the Rastelli classification (classification of atrioventricular septal defects) and the Rastelli procedure (among other applications, used for the treatment of transposition of the great arteries with ventricular septal defect and left ventricular outflow tract obstruction). Giancarlo Rastelli died in 1970 at the age of 36. His beatification has been in progress at the Vatican since 2005. This paper presents the current view on the Rastelli classification, the problems related to the Rastelli procedure, as well as alternative procedures applied in specific cases, i.e. the Nikaidoh, REV, and Metras procedures.